Metabolic Alterations in Patients with Pheochromocytoma - Erlic, Zoran; Beuschlein, Felix (Experimental and Clinical Endocrinology & Diabetes, 2019)
Metabolic alterations in patients with hormonally active pheochromocytoma/paraganglioma (PPGL) have been described early on in the literature. The initial findings were related to disturbed glucose homeostasis and lipolysis activation, as well as elevated metabolic rates in affected patients. Similarly, from early autopsy reports, the presence of brown adipose tissue had been noted in PPGL patients. In more recent years, changes in body weight, fat mass and distribution have been analyzed in more detail in addition to activity of brown adipose tissue based on functional imaging techniques. Over the last decades, several larger case series and cohort studies have contributed towards the elucidation of possible mechanism contributing to these clinical observations. Herein, we summarize the clinical and experimental data regarding metabolic alterations and related clinical manifestations in PPGL patients.
Keywords: pheochromocytoma; catecholamine; lipid metabolism; glucose metabolism; adipose tissue; bone disease